FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA SISA MAKANAN PADA PASIEN RAWAT INAP DI RSUD BANGLI - Luh Putu Yasmari Septidiantari; Ida Ayu Eka Padmiari, SKM. M.Kes; Dr. Ni Nengah Ariati, SST, M.Erg (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2022)
The food waste is the amount of food that is not consumed. The food waste in addition to causing inadequate nutritional needs of patients also causes wasted costs. The purpose of this study is to determine the factors that influence the occurrence of leftovers in inpatients at Bangli District Hospital. The type of research used was observational with a cross-sectional study design, and samples were taken by purposive sampling which was 30 samples. The type of data collected are data characteristic of the sample by interview using the identity form, and external factors by answering the questionnaire, food waste data with weighing methods, while hospital overview data, number of patients hospitalized, and number of nutritionists and waiters are taken from the data annual reports or records related to the required data. Data analysis uses frequency distribution tables and cross tables then be described descriptively. The results of this study indicate that the dominant internal factor influencing the occurrence of food waste is the gender 56.66%. While the external factors that predominantly influence the occurrence of food waste are food aroma 53.33%.Keywords: food waste, internal factor, external factor